The Impact of Covid-19 Pandemic on Romania's Tourism Seasonality in the Seaside and Mountain Resorts in 2020 versus 2019 - Agatha POPESCU (Communications of International Proceedings, 2021)
The Covid -19 pandemic has deeply affected tourism all over the world. In this context, the paper analyzed its impact on Romanian tourism seasonality at the national level and also in the seaside and mountain resorts in the year 2020 versus 2019. The data on tourist arrivals provided by National Institute of Statistics and were processed using descriptive statistics, fixed and structural indices, seasonality indicators and Gini concentration coefficient. Compared to 2019, in 2020, Romania recorded 6.3 million tourist arrivals, by 53% less. About 43% of tourists visited the mountain and the seaside resorts. However, the loss in 2020 accounted for only 37% in the seaside and for 51% in the mountain resorts. The high variation in tourist arrivals in 2020 versus 2019 was caused by the restriction measures mainly in March and April, the most critical months for tourism. The peaks were registered in August. Summer and also winter vacations saved tourism. Seasonality indicator, intensity, range and Gini concentration index were higher in 2020 versus 2019. While at the country level, the seasonality was lower, a moderate seasonality was noticed in the seaside and a low seasonality in the mountains. In 2021, tourism industry has to develop a more flexible strategy focused on tourists' high demand for open-air and nature-based destinations like seaside and mountain resorts.
Keywords: Seasonality; Tourism; Covid-19 Pandemic; Impact; Romania